Keratoconus evaluation using the Orbscan topography system - Auffarth, Gerd U.; Wang, Li; Völcker, Hans Eberhard (Journal of cataract and refractive surgery, 2000)
Purpose - To evaluate corneal topography in a series of keratoconus patients using the Orbscan Topography System. - Setting - Department of Ophthalmology, Ruprecht-Karls-University of Heidelberg, Heidelberg, Germany. - Methods - Seventy-one eyes of 38 patients with keratoconus were evaluated. Quantitative topographic parameters were analyzed with special reference to the central point of the cornea, the apex (the point with maximum reading on the anterior elevation best-fit sphere map), and the thinnest point. Evaluation included location, elevation (compared to a best-fit sphere), pachymetry, tangential curvature, and composite curvature. The mirror-image symmetry between the right and left eyes of a patient was also investigated. - Results - Mean patient age was 31.2 years ± 12.2 (SD). Thirty-three patients (86.8%) had bilateral keratoconus and 5 (13.2%), unilateral keratoconus. Most cones (68/71) were located in the inferior temporal quadrant; 3 were above the horizontal meridian. Mean distance between the apex and the thinnest point was 0.917 ± 0.729 mm (P < .001). The correlations between apex elevation and apex composite curvature and apex tangential curvature were high (r = 0.94 and r = 0.91, respectively; P < .001). In right and left eyes, there was a correlation between the apex and the thinnest point semimeridians (r = 0.47 and r = 0.65, respectively; P < .05) but not between the radii of the apex and the thinnest point (r = 0.21 and r = 0.24, respectively). - Conclusions - The Orbscan system can provide useful and accurate information in defining the morphology of keratoconus and detecting subtle topographic changes present in early keratoconus. It may also improve the results of contact lens fitting and surgical management.
Gesehen am 26.02.2021